2014
DOI: 10.1371/journal.pmed.1001717
|View full text |Cite
|
Sign up to set email alerts
|

Prioritizing Pregnant Women for Long-Lasting Insecticide Treated Nets through Antenatal Care Clinics

Abstract: Jenny Hill and colleagues discuss the importance of antenatal care services in providing pregnant women with a long-lasting insecticide treated net for the prevention of malaria in both the mother and infant. Please see later in the article for the Editors' Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 36 publications
1
16
1
Order By: Relevance
“…Interestingly, women reported using LLINs more often than men when at home; however, when travelling, the opposite was true. This suggests that at home, women may be more aware of the importance of sleeping under LLINs to protect against malaria, perhaps reflecting routine distribution of LLINs at antenatal clinics and targeted campaigns to increase LLIN use among pregnant women [30][31][32]. Some studies carried out in sub-Saharan Africa have evaluated use of LLINs at home and reported increased use among female participants [33][34][35] [34], suggesting that women may be more likely than men to use LLINs when at home.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, women reported using LLINs more often than men when at home; however, when travelling, the opposite was true. This suggests that at home, women may be more aware of the importance of sleeping under LLINs to protect against malaria, perhaps reflecting routine distribution of LLINs at antenatal clinics and targeted campaigns to increase LLIN use among pregnant women [30][31][32]. Some studies carried out in sub-Saharan Africa have evaluated use of LLINs at home and reported increased use among female participants [33][34][35] [34], suggesting that women may be more likely than men to use LLINs when at home.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the example of TT immunization, it is quite evident that 60% increase in coverage in last 25 years has led to 90% reduction in tetanus mortality in babies ( Blencowe et al, 2010a ). However, the coverage for insecticide treated bed nets in 2011 is still low 35.3% (5.2%–75.5%) and countries should prioritize mechanisms to increase coverage ( Hill et al, 2014 ). Moreover, effective interventions such as hygienic cord care, which includes chlorhexidine cord cleansing, and adopting antenatal corticosteroids for preventing neonatal respiratory distress syndrome in preterm infants have very low coverage according to surveys with less than a third of women and neonates in need receiving them ( Mason et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, women reported using LLINs more often than men when at home; however, when travelling, the opposite was true. This suggests that at home, women may be more aware of the importance of sleeping under LLINs to protect against malaria, perhaps re ecting routine distribution of LLINs at antenatal clinics and targeted campaigns to increase LLIN use among pregnant women [32][33][34]. When travelling, women may either lack LLINs or the agency to use them, particularly when visiting the home of a friend or relative.…”
Section: Discussionmentioning
confidence: 99%